2015
DOI: 10.1371/journal.pone.0125358
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Plasmodium falciparum DNA Repair Protein Mre11 with an Evolutionarily Conserved Nuclease Function

Abstract: The eukaryotic Meiotic Recombination protein 11 (Mre11) plays pivotal roles in the DNA damage response (DDR). Specifically, Mre11 senses and signals DNA double strand breaks (DSB) and facilitates their repair through effector proteins belonging to either homologous recombination (HR) or non-homologous end joining (NHEJ) repair mechanisms. In the human malaria parasite Plasmodium falciparum, HR and alternative-NHEJ have been identified; however, little is known about the upstream factors involved in the DDR of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
2
25
2
Order By: Relevance
“…MMEJ has been shown to require six key proteins in mammals: MRE11, NBS1, LIGASE III, XRCC1, FEN1 and PARP1 [ 51 ]. Of these, only MRE11, XRCC1 and FEN1 have been identified in Plasmodium , and MRE11 has recently been characterised in P. falciparum [ 52 ]. Of those missing, DNA ligase III seems to be replaceable by DNA ligase I [ 53 ] and PARP1 is only present in the related parasite T. gondii , supporting its suggested role to compete with Ku for choice of repair pathway [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMEJ has been shown to require six key proteins in mammals: MRE11, NBS1, LIGASE III, XRCC1, FEN1 and PARP1 [ 51 ]. Of these, only MRE11, XRCC1 and FEN1 have been identified in Plasmodium , and MRE11 has recently been characterised in P. falciparum [ 52 ]. Of those missing, DNA ligase III seems to be replaceable by DNA ligase I [ 53 ] and PARP1 is only present in the related parasite T. gondii , supporting its suggested role to compete with Ku for choice of repair pathway [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how malaria parasites respond to DSBs and efficiently maintain genome integrity is unclear. Characterization of important enzymes involved in HR demonstrated that this pathway is functionally conserved ( 17 19 ). The subtelomeric regions, given their size, extensive gene content, semirepetitive nature, and unique chromatin structure, represent a particularly interesting region of the genome for studying DSB repair.…”
Section: Introductionmentioning
confidence: 99%
“…BLM (Bloom syndrome protein) is a DNA helicase involved in DSB end-resection, and Pf Blm possessed helicase activity ( Rahman et al, 2016 ). The protein complex Mre11 (meiotic recombination 11), Rad50 (radiation-sensitive 50), and NBS1 (involved in Nijmegen breakage syndrome) recognizes and end-resects DNA DSBs, and Pf Mre11 demonstrated nuclease activity and interacted with Pf Rad50 ( Badugu et al, 2015 ). Lastly, diploid zygotes of Plasmodium undergo meiosis in the insect vector to produce haploid cells, a state in which Dmc1 becomes relevant.…”
Section: Homologous Recombination In Protozoan Parasitesmentioning
confidence: 99%